Top 50 cited articles on cardiac rehabilitation: A bibliometric and altmetric analysis study: Top 50 cited articles on cardiac rehabilitation - Erdem , İbrahim Halil; Bagcier, Fatih; Temel, Mustafa Huseyin (Journal of Surgery and Medicine, 2023)
Background/Aim: Cardiovascular disease (CVD) is the leading cause of death globally, with an estimated 18.6 million deaths each year. Cardiac rehabilitation (CR) has positive effects on reducing the mortality and morbidity of CVD, so there is a growing interest in this field. The aim of this study was to analyze the top 50 cited articles in the field of CR. Methods: The Web of Science (WoS) database was searched for articles published between 1986 and 2021. A record was made of the following information for the bibliometric analysis: article title, year of publication, number of authors and their names, number of citations, citation index, journal of publication, impact factor, type of article, and source of funding. The altmetric attention score (AAS) was recorded using automatic software calculation. Results: The majority of articles were published in the journal “Circulation” (n=14) and the “Journal of the American College of Cardiology” (n=8). The country with the highest number of articles was the US (n=27), and the most cited author was P.A. Ades. Studies evaluating exercise-based rehabilitation, key components of CR, and secondary prevention were among the top cited articles. In terms of AAS, in addition to the titles mentioned, mobile health services that rely on communication technologies have also received attention. Conclusion: This study provides useful information for researchers interested in CR, including trends, topics of interest in the field, and potential research collaborations. It is intended to guide future, more comprehensive, and in-depth studies on CR.